2010
DOI: 10.1093/schbul/sbq043
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Relationships Among Intrinsic Motivation, Neurocognition, and Psychosocial Functioning in Schizophrenia

Abstract: To address significant gaps in our understanding about how neurocognition, intrinsic motivation (IM), and psychosocial functioning are interrelated in schizophrenia, this study investigated the following questions: Is IM stable or dynamic over time? Does neurocognition predict change in IM over time? What is the association between change in neurocognition, change in IM, and change in psychosocial functioning? Finally, what is the causal structure of the relationships among neurocognition, IM, and psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 117 publications
(156 reference statements)
2
83
1
2
Order By: Relevance
“…Nevertheless, a recent study found that IM in schizophrenia is a dynamic process that changes over time (Nakagami et al, 2010), and can actually be fostered by attempts to improve perceived interest and enjoyment. According to our findings, better metacognitive skills can subsequently improve learning potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a recent study found that IM in schizophrenia is a dynamic process that changes over time (Nakagami et al, 2010), and can actually be fostered by attempts to improve perceived interest and enjoyment. According to our findings, better metacognitive skills can subsequently improve learning potential.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on motivation in schizophrenia have referred to the self-determination theory of motivation Nakagami et al, 2008Nakagami et al, , 2010. For example, a recent study using a standard and a motivational mathematical game reported that schizophrenia patients with higher IM levels learned better than those with lower IM levels .…”
Section: Introductionmentioning
confidence: 99%
“…As mental states are inseparable from emotional processes and 'in many if not all cases, human social and emotional behaviors are highly intertwined' [ 113 , p. 48] any account of social impairments in persons with schizophrenia should include the role of emotions [104] . Emotion processing is a major determinant of social outcome in schizophrenia such as Emotion Recognition [83][84][85][86][87][88][89] , anhedonia [114,115] and particularly the anticipatory pleasure experience [116] , motivation [117,118] , recently regarded as the critical feature of negative syndrome [119] with respect to functional outcome. To note, persons with schizophrenia display relevant impairment in the integration of affective and cognitive ToM skills [120] , and affective ToM tasks have appeared to be more predictive of social functioning in people with schizophrenia [84] .…”
Section: Cognitivismmentioning
confidence: 99%
“…In a study 48 of 130 patients with schizophrenia or schizoaffective disorder assessing the relation between cognition, motivation, and psychosocial function, cognition and not motivation was found to cause change in psychosocial function during a 1-year period. In contrast, psychosocial change caused change in motivation that, in turn, predicted change in cognition.…”
mentioning
confidence: 99%